If x is positive show that. x>log(1+x)>x-(x^2/2)
To prove
"x>log(1+x)>x-\\frac{x^{2}}{2}" when "x>0"
We first suppose that
"f(x)=x-log(1+x)"
Then
"f^\\prime(x)=1-\\frac{1}{1+x}"
"\\implies" "f^\\prime(x)=\\frac{x}{1+x}"
"\\implies" "f^\\prime(x)>0" as "x>0"
"\\implies" "f(x)>f(0)"
"\\implies" "f(x)>0" as "f(0)=0"
"\\implies" "x-log(1+x)>0"
"\\implies" "x>log(1+x) ----(1)"
Next, Suppose that
"g(x)=log(1+x)-(x-\\frac{x^{2}}{2})"
when "x>0"
"\\implies" "g^\\prime(x)=\\frac{1}{1+x}-(1-x)"
"\\implies" "g^\\prime(x)=\\frac{1}{1+x}-1+x"
"\\implies" "g^\\prime(x)=\\frac{1-1-x}{1+x}+x"
"\\implies" "g^\\prime(x)=x-\\frac{x}{1+x}"
"\\implies" "g^\\prime(x)=\\frac{x^{2}}{1+x}"
"\\implies" "g^\\prime(x)>0" as "x>0"
So "g(x)" is increasing for "x>0"
"\\implies" "g(x)>g(0)"
"\\implies" "g(x)>0" as "g(0)=0"
"\\implies" "log(1+x)-(x-\\frac{x^{2}}{2})>0"
when "x>0"
"\\implies" "log(1+x)>(x-\\frac{x^{2}}{2})---(2)"
Combining (1) and (2), we have
"x>log(1+x)>x-\\frac{x^{2}}{2}"
when "x>0"
Hence proved.
Comments
Leave a comment